The Impact of Email Advertising on Consumer Attitudes in E-Commerce - Roozbeh, Mohammad; Raza, Jamalzadeh (Journal of Policy Options, 2021)
E-commerce has increasingly become a cornerstone for many businesses in recent years. In this context, online marketing communication plays a crucial role in securing a competitive advantage. E-mail advertising, in particular, stands out as a cost-effective, direct, and reciprocal method for businesses to overcome time and geographical barriers. This form of marketing allows companies to reach their audience efficiently and engage with them in a personalized manner, making it an essential tool in the modern digital marketing landscape. This study explores the characteristics of advertising emails and their impact on customers' attitudes toward email-based advertisements. By analyzing how different aspects of email advertising influence consumer perceptions and responses, the research aims to provide insights into effective strategies for enhancing engagement and effectiveness in email marketing campaigns. According to the research findings, the entertainment value and informativeness of advertising email content have a strong and positive impact on customers' attitudes toward email-based advertisements. This suggests that when advertising emails are both engaging and provide valuable information, they are more likely to be well-received by recipients. On the other hand, the privacy concerns associated with advertising emails have a strong, negative influence on customers' attitudes toward email-based advertisements. This indicates that issues related to the privacy of personal information in advertising emails can lead to a more negative perception among recipients.